Phosphorus and bromine modified epoxy resin with enhanced cryogenic mechanical properties and liquid oxygen compatibility simultaneously. (February 2021) - Zhou, Zili; Qian, Jian; Zhang, Jian; Cui, Yongshuang; Li, Yuanqing; Tan, Di; Long, Junfei; Wu, Huiqiang; Liu, Qun; Guo, Fangliang; Sun, Baogang; Shi, Hanqiao; et al.
Abstract: Herein, epoxy resins for composite liquid oxygen (LOX) fuel tanks are modified with phosphorous flame retardant (DOPO) and brominated epoxy resin (EX48). With the incorporation of DOPO and EX48, the processing properties requirements for the hot-melt prepreg are contented with the significantly enhanced viscosity of the modified epoxy resin. At the same time, the tensile performance, flexural performance and fracture toughness of epoxy resin at room temperature and 90 K are improved with the introduction of DOPO and EX48. In addition, the epoxy resin of EP/P7.7 /Br40 offers a highest limited oxygen index of 33.5% and a lowest LOX impact sensitivity of 5% with the eliminated LOX incompatible reactions including explosion and combustion. Consideration of the excellent cryogenic mechanical properties and LOX compatibility, combined with ideal viscosity for hot-melt prepreg preparation, the epoxy resin modified with DOPO and EX48 simultaneously is attractive as the polymer matrix for composite LOX fuel tanks. Highlights: Epoxy resin modified with phosphorus and bromine simultaneously. The cryogenic mechanical properties and LOX compatibility of epoxy are enhanced. The epoxy resin prepared is suitable for composite liquid oxygen tank.